(untitled) (Baghdad Science Journal, 2024)
Toxic metals have a serious impact on the ecological environment. The determination of these metal concentrations provides more information about their toxicity. In this study, a simple, rapid and selective spectrophotometric method with solid phase extraction method has been described for the simultaneous determination of lead (Pb) and cadmium (Cd) in environmental samples using a freshly precipitated zinc-diethyldithiocarbamate (Zn-(DDTC)2) as a reagent. The pre-concentration of Pb and Cd contents was performed according to solid phase extraction process. The determination of Pb+2 and Cd+2 based on the replacement of Zn+2 from the freshly precipitated Zn-(DDTC)2 by Pb+2 and Cd+2 in aqueous solution. The proposed method presented a linear range of 0.1 – 16 µgml-1 and 0.1 – 14 µgml-1 for Pb and Cd respectively. The recoveries of the studied metals were ranged between 90 – 96% with correlation coefficients (R2) of 0.9985 and 0.9989 for Pb and Cd respectively. The optimum conditions of various parameters (pH, extraction period and aqueous phase volume) were experimentally investigated, and the effect of various salt and or ion solutions as interferences was also studied. The proposed method was also applied for a number of real environmental samples to assess metal ion contents. The obtained results showed a good precision and accuracy indicating that the current method can apply for routine measurement of Pb and Cd contents and also can be applied to more fields.